O impacto da interatividade percebida nas midias sociais das marcas nos comportamentos de engajamento do cliente mediado pela satisfação, comprometimento e confiança - Etienne, Josué Jean Daniel (2023)
Previous studies carried out in Europe point to positive relationships between perceived interactivity on brands' social media platforms with customer engagement behaviors. Results that motivated this study. Thus, the overall objective of this dissertation broadly examined how Brazilian and Haitian customers' perceptions of perceived interactivity on brands' social media platforms impact customer engagement behaviors (i.e., customer purchases, eWOM, influence, feedback) at the same time that it is responsible for the mediating roles of satisfaction, trust and commitment of customers in both countries. To achieve the objective of this study, a survey answered by 1,617 users residing in Haiti and Brazil was carried out. Data analysis was performed using Structural Equation Modeling (SME) with software such as SmartPLS 4.0., and SPSS 22. As a contribution, this study reinforces that the perceived interactivity on the brands' social media platforms strongly contributes to building the commitment, satisfaction and customer trust in brands that explain some customer engagement behaviors such as purchase intention, influence, feedback and eWOM. It also points out differences between the consumption profiles in Haiti (poor country) and in Brazil (emerging country) in the mediating roles of satisfaction, trust.